2018
DOI: 10.1002/bse.2190
|View full text |Cite
|
Sign up to set email alerts
|

How do integrated quality and environmental management practices affect firm performance? Mediating roles of quality performance and environmental proactivity

Abstract: Based on a sample of 208 Turkish firms, this paper investigates the integration of two management systems, quality management and environmental management, and explores the effect of this integration on firm performance. First, a conceptual framework was developed, relying on the premises of the resource‐based view. Second, mediating roles of quality performance and environmental proactivity were examined on the association between integrated quality and environmental management systems and firm performance. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 119 publications
5
74
1
2
Order By: Relevance
“…Although these factors prompted a shift towards a culture of quality management (Srinivasan & Kurey, ), we argue that they can also enable a green organisational culture. This argument is supported by Arda et al () who found that quality management and environmental management are two interdependent systems, that once integrated can positively affect firm performance. Importantly, we argue that GHRM activities play an essential role in the development of the four EGC.…”
Section: Literature Review and Hypothetical Modelmentioning
confidence: 81%
See 3 more Smart Citations
“…Although these factors prompted a shift towards a culture of quality management (Srinivasan & Kurey, ), we argue that they can also enable a green organisational culture. This argument is supported by Arda et al () who found that quality management and environmental management are two interdependent systems, that once integrated can positively affect firm performance. Importantly, we argue that GHRM activities play an essential role in the development of the four EGC.…”
Section: Literature Review and Hypothetical Modelmentioning
confidence: 81%
“…Importantly, our data indicate that there is a full mediation effect for the EGC on the relationship between GHRM and EP. In a recent study by Arda et al (), the authors determined that quality performance and environmental proactivity mediate the relationship between environmental management and firm performance. Our findings build on this work by indicating that companies implementing environmental management programs need to consider the critical role of proenvironmental leadership emphasis, credible environmental messaging, peer involvement, and employee empowerment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Societies with high scores in this dimension tend to value the future rewards of present actions and are characterized by a readiness to delay immediate benefits; in contrast, societies with low long-term orientation cultures value the use of time and emphasize quick results (Hofstede, 2001;Williams & Zinkin, 2008). Different from that of the environmental management and sustainability literature which argues the influence of long-term orientation on EMPs (Arda, Bayraktar, & Tatoglu, 2019;Gotschol, De Giovanni, & Vinzi, 2014), this study argues that long-term orientation cultures affect the relationship between EMPs and firm performance.…”
Section: Long-term Orientationmentioning
confidence: 99%